Model Pembinaan Pegawai untuk Meningkatkan Kinerja di UB Guest House - Saputro, Lukman Khamdani; Gani, Abdul Juli Andi; Novita, Asti Amelia (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2021)
The purpose of this research is to find out how to develop employees at UB Guest House, what obstacles are encountered, and how to overcome these obstacles. These employee development activities include: education and training, career education, and discipline education. This study uses a qualitative method using triangulation techniques. The results show that: the management of UB Guest House is expected to set a clear budget in an effort to support the financing of career development policies, where the development must be carried out for employees who have potential in terms of education and work experience; as well as providing motivation to employees and increasing organizational commitment. This can be achieved by carrying out various coaching such as: training, promotion, and transfer.